Metástases de adenocarcinoma de vesícula biliar em colecistectomia videolaparoscópica - Ziliotto Júnior,Antônio (1998)
The cancer of the gallbladder unless rare, has been found in about 1% of all cholecistectomies for chronic cholecistitis. The preoperative diagnosis is difficult to be done because there are not particular symptoms. In the present paper the authors relate a case of a patient submitted to a laparoscopic cholecistectomy for acute cholecistitis. The pathologist reported a concomitant tubular adenoma in the specimen. At the 6th postoperative month the patient had intense abdominal pain, and at the 7th month, metastasis of an adenocarcinoma was detected in the port sites. The first specimen was reviewed and showed a primay adenocarcinoma of the gallbladder. The patient was submitted to chemotherapy but with few response, dying in the 9th postoperative month. The authors conclude that unless difficult, the preoperative diagnosis of cancer of the gallbladder is essential for a more appropriate therapy, mainly in the patients aging more than 50 year when the neoplasm appears with greater prevalence. Despite the videolaparoscopic access for the surgery provides low morbidity and mortality, it is not indicated for the gallbladder cancer when the conventional access by laparotomy is obligatory.